Higher accumulation of proteinase inhibitors in flowers than leaves and fruits as a possible basis for differential feeding preference of Helicoverpa armigera on tomato (Lycopersicon esculentum Mill, Cv. Dhanashree) - Damle, M. S.; Giri, Ashok P.; Sainani, Mohini N.; Gupta, Vidya S. (Phytochemistry, 2005)
Tomato (Lycopersicon esculentum, Mill; cultivar- Dhanashree) proteinase inhibitors (Pis) were tested for their trypsin inhibitory (TT) and Helicoverpa armigera gut proteinases inhibitory (HGPI) activity in different organs of the tomato plants. Analysis of TI and HGPI distribution in various parts of the plant showed that flowers accumulated about 300 and 1000 times higher levels of TI while 700 and 400 times higher levels of HGPI as compared to those in leaves and fruits, respectively. Field observation that H. armigera larvae infest leaves and fruits but not the flowers could be at least partially attributed to the protective role-played by the higher levels of Pis in the flower tissue. Tomato Pis inhibited about 50-80% HGP activity of H. armigera larvae feeding on various host plants including tomato, of larvae exposed to non-host plant Pis and of various larval instars. Tomato Pis were found to be highly stable to insect proteinases wherein incubation of inhibitor with HGP even for 3 h at optimum conditions did not affect inhibitory activity. Bioassay using H. armigera larvae fed on artificial diet containing tomato PIs revealed adverse effect on larval growth, pupae development, adult formation and fecundity. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: accumulation of PI; Helicoverpa armigera; Lycopersicon esculentum; Midgut proteinases; Plant defense; Proteinase inhibitors

Spatial and temporal expression patterns of diverse Pin-II proteinase inhibitor genes in Capsicum annuum Linn - Tamhane, Vaijayanti A.; Giri, Ashok P.; Kumar, Pavan; Gupta, Vidya S. (Gene, 2009)
Pin-II type proteinase inhibitor (PI) genes were cloned from fruit and stem tissues of Capsicum annuum L var Phule Jyoti using primers designed from reported CanPI gene sequence (AF039398). In total, 21 novel CanPIs, members of the Pin-II PI family, were identified in the study, with three isoforms of 1-inhibitory repeat domain (IRD), eight isoforms of 2-IRD), three isoforms of 3-IRD, five isoforms of 4-IRD and two partial CanPI sequences. Most of the sequences showed variation (2 to 20%) in the deduced AA sequences which were pronounced close to the reactive site loop. Expression patterns of CanPIs in the fruit and stem tissues of mature C. annuum plants were shown to vary qualitatively and quantitatively using semi-quantitative RT-PCR expression analysis. In the fruit tissue. CanPIs with different IRDs (from 1 to 4) were expressed simultaneously. In stem tissue, 1- and 2-IRD CanPIs were strongly expressed along moderate expression of 3- and 4-IRD genes. Analysis of CanPI protein activity showed a range of active forms across the tissues. CanPI expression was differentially up-regulated upon wounding and insect attack. Although infestation by aphids (Myzus persicae) and lepidopteran pests (Spodoptera litura) specifically induced 4-IRD CanPIs, virus-infected leaves did not affect CanPI expression. Analysis of CanPI protein activity indicated that the up-regulation in CanPI expression was not always correlated with increase in PI activity. Our results demonstrated that CanPI expression is regulated spatially, temporally as well as qualitatively and quantitatively. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: CanPI; Capsicum annuum; Endogenous role; Pin-II; Plant defense; Proteinase inhibitor

Characterized constituents of insect herbivore oral secretions and their influence on the regulation of plant defenses - Kallure, Gopal S.; Kumari, Archana; Shinde, Balkrishna A.; Giri, Ashok P. (Phytochemistry, 2022)
For more than 350 million years, there have been ongoing dynamic interactions between plants and insects. In several cases, insects cause-specific feeding damage with ensuing herbivore-associated molecular patterns that invoke characteristic defense responses. During feeding on plant tissue, insects release oral secretions (OSs) containing a repertoire of molecules affecting plant defense (effectors). Some of these OS components might elicit a defense response to combat insect attacks (elicitors), while some might curb the plant defenses (suppressors). Few reports suggest that the synthesis and function of OS components might depend on the host plant and associated microorganisms. We review these intricate plant-insect interactions, during which there is a continuous exchange of molecules between plants and feeding insects along with the associated microorganisms. We further provide a list of commonly identified inducible plant produced defensive molecules released upon insect attack as well as in response to OS treatments of the plants. Thus, we describe how plants specialized and defense-related metabolism is modulated at innumerable phases by OS during plant-insect interactions. A molecular understanding of these complex interactions will provide a means to design eco-friendly crop protection strategies.
Keywords: Effector; Elicitor; Herbivore insects; Oral secretion; Plant defense; Suppressor

Characterization of wound-induced electrical signals and reactive oxygen species in chickpea (Cicer arietinum) - Deshpande, Shweta; Pawar, Shivani; Kumari, Archana (Plant Signaling & Behavior, 2025)
Mechanical damage to plants triggers both localized and systemic responses that activate plant defense mechanisms. Early signaling events include calcium (Ca2+) flux, reactive oxygen species (ROS), and electrical alterations. These signals coordinate downstream defense pathways, enabling plant acclimation to biotic stress. Electrical signaling following wounding/herbivory has been extensively studied in Arabidopsis; however, its dynamics in crop plants such as chickpea (Cicer arietinum) are not well understood. The pattern of the SWP in chickpea was similar to that in Arabidopsis but with a longer repolarization phase and was detectable only within the leaflets. The signals generated by damaging the leaflet were more pronounced, propagated bidirectionally and varied between herbivore-susceptible and tolerant chickpea varieties. The SWP duration is correlated with increased expression of AOS and OPR3 transcripts, which are markers of the stress hormone JA. Additionally, ROS production in wounded chickpea leaflets is associated with increased expression of ROS-generating genes. The use of DPI, an inhibitor of NADPH oxidase, which is responsible for ROS production, inhibited SWP, suggesting the crucial role of ROS in wound-induced SWP. This study provides insight into the interplay between wound-induced electrical signaling and ROS production in chickpea and proposes the measurement of electrical signals as a rapid, noninvasive approach for screening crop cultivars for pest susceptibility and tolerance.
Keywords: Chickpea; Electrical signal; Plant defense; ROS; wound

Transcriptome analyses reveal TaWRKY41 as a potential candidate governing spot blotch resistance in wheat - Dayama, Bhakti R.; Mahadik, Varsha A.; Somani, Deepika; Shinde, Balkrishna A.; Kondhare, Kirtikumar R.; Karthikeyan, Muthukumarasamy; Kadoo, Narendra Y. (Physiology and Molecular Biology of Plants, 2025)
Spot blotch disease caused by Bipolaris sorokiniana poses a significant threat to wheat production. Cultivation of disease-resistant wheat genotypes appears to be the most practical approach to mitigate the impact of this devastating disease. However, the molecular responses of wheat plants during spot blotch disease progression remain poorly understood. This study employed RNA-sequencing to unravel the spatiotemporal molecular events underlying the resistance mechanism in the spot blotch susceptible and resistant wheat genotypes. This study further provides a comprehensive overview of differentially expressed transcripts through functional analysis and transcription factor identification, elucidating the biological mechanisms governing wheat-B. sorokiniana interaction. In the resistant genotype, the expression of one of the key transcription factors, TaWRKY41, was significantly induced upon pathogen inoculation. Computational studies, electrophoretic-mobility shift assay, and yeast one-hybrid assay confirmed the interaction of the recombinant TaWRKY41 protein with W-box elements present in the promoters of plant defense-related genes. Furthermore, co-expression network analyses identified downstream genes positively correlated with TaWRKY41, providing insights into their probable involvement in the defense response. Overall, our investigation suggests that TaWRKY41 contributes to spot blotch resistance in wheat. This knowledge can help develop new disease-resistant wheat varieties.
Keywords: Plant defense; plant-pathogen interaction; TaWRKY41; Transcription factors; Transcriptomics